Inside Cover: Regioselective Metal‐ and Reagent‐Free Arylation of Benzothiophenes by Dehydrogenative Electrosynthesis (Angew. Chem. Int. Ed. 40/2018). Issue 40 (19th September 2018) - Lips, Sebastian; Schollmeyer, Dieter; Franke, Robert; Waldvogel, Siegfried R.
Abstract : Electrochemical "welding" serves as a powerful tool for the arylation of benzo[ b ]thiophenes in position 2 or 3. S. R. Waldvogel and co‐workers report in their Communication on page 13325 ff. the first electro‐organic dehydrogenative synthesis of 2‐ or 3‐(hydroxyphenyl)benzo[ b ]thiophenes by oxidative cross‐coupling reactions. The direct use of electricity as a reagent eliminates the necessity of leaving groups, metal catalysts, stoichiometric oxidizers, or reducing agents. Therefore, the reaction enables a sustainable synthetic pathway to these scaffolds and can be considered as "green chemistry".